The nexus between the fear of floating and expenditures witching external adjustment mechanism: emerging European and Latin American floaters - Beker Pucar, Emilija (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
The focus of this research is the identification of the fear of floating (FOF) problem as a vulnerable ground for employing the exchange rate (ER) as a shock absorber with consequent limitations for expenditure-switching external adjustment mechanism. This research aims to fill the literature gap stressing the connection between FOF and the functioning of expenditure-switching external adjustment mechanism, highlighting the nexus from the viewpoint of emerging European vs. Latin American floaters, as well as from individual emerging European floaters (the Czech Republic, Hungary, Poland, Romania) in the period 2000Q1-2017Q2 with standard and panel VAR analysis. FOF is identified as a stronger reaction of foreign exchange reserves and interest rate to nominal ER shocks, as well as higher variations of real ER explained with price shocks compared to nominal ER shocks. As a confirmation, in countries with expressed FOF current account shock is more transmitted to economic activities (expenditure-reducing external adjustment) rather than nominal ER changes (expenditure-switching mechanism). The results confirm the vulnerable position of European emerging floaters compared to Latin American floaters, bearing in mind the stronger FOF coinciding with the higher currency mismatch. Within the sample of European emerging floaters the most vulnerable position concerning the nexus was detected for Romania, while the most favorable position was found in the case of Poland
Argumenta Oeconomica, 2020, Nr 1 (44), s. 47-76